2017
DOI: 10.14581/jer.17019
|View full text |Cite
|
Sign up to set email alerts
|

A 6-Month-Old Girl with Incontinentia Pigmenti Presenting as Status Epilepticus

Abstract: Incontinentia pigmenti (IP) is an uncommon neurocutaneous syndrome. Its initial diagnosis is based primarily on characteristic papulovesicular skin lesions and early-onset neonatal seizures. In contrast to typical early neurologic manifestations, we encountered a normally developed 6-month-old female patient with hyperpigmented whorls on her body. Following respiratory syncytial virus infection and fever, the patient exhibited status epilepticus. Brain magnetic resonance imaging studies of the patient were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…To date, most studies regarding IKBKG mutations in IP cases were conducted in Western populations. Although several Korean studies have examined clinically diagnosed IP patients, 10,11 only seven genetically confirmed IP cases have been reported; six had a common exon 4–10 IKBKG deletion 12‐14 and only one had a point mutation 15 . In this study, we performed a genetic analysis in Korean IP patients and reported molecular genetic backgrounds including five intragenic sequence variants of IKBKG with three novel mutations.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies regarding IKBKG mutations in IP cases were conducted in Western populations. Although several Korean studies have examined clinically diagnosed IP patients, 10,11 only seven genetically confirmed IP cases have been reported; six had a common exon 4–10 IKBKG deletion 12‐14 and only one had a point mutation 15 . In this study, we performed a genetic analysis in Korean IP patients and reported molecular genetic backgrounds including five intragenic sequence variants of IKBKG with three novel mutations.…”
Section: Introductionmentioning
confidence: 99%